2009
DOI: 10.1017/s147895150900011x
|View full text |Cite
|
Sign up to set email alerts
|

Individual brief art therapy can be helpful for women with breast cancer: A randomized controlled clinical study

Abstract: The conclusion suggests that art therapy has a long-term effect on the crisis following the breast cancer and its consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 35 publications
(54 reference statements)
1
71
0
1
Order By: Relevance
“…Two participants in VT accepted Body Awareness as an additional treatment during psychotherapy.' 47 In the Thyme et al 2009 62 study the usage of antidepressants was self-reported, and therefore this information may be incomplete. In the Chapman et al 49 study, 'treatment as usual' hospital care was defined as the normal and usual course of paediatric care including Child Life services, art therapy, and social work and psychiatric consultations.…”
Section: Concomitant Treatmentmentioning
confidence: 99%
“…Two participants in VT accepted Body Awareness as an additional treatment during psychotherapy.' 47 In the Thyme et al 2009 62 study the usage of antidepressants was self-reported, and therefore this information may be incomplete. In the Chapman et al 49 study, 'treatment as usual' hospital care was defined as the normal and usual course of paediatric care including Child Life services, art therapy, and social work and psychiatric consultations.…”
Section: Concomitant Treatmentmentioning
confidence: 99%
“…Art therapy is an effective intervention for psychological and spiritual care, and has been reported to be effective for alleviation of anxiety, depression, and somatic symptoms for women with breast cancer [4] and for tension, depression, anger, confusion, and vigor [5]. In a systematic review of creative psychological interventions including art therapy, music therapy, dance therapy and movement therapy, Archer et al [6] found benefits for anxiety and depression, quality of life, coping, stress, anger and mood.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Various CAM therapies have improved psychological symptoms frequently associated with cancer and cancer treatment, including cancer-related fatigue, 8 pain, 9 and symptoms of anxiety and depression. 10,11 Creative arts therapies (CATs), including music therapy, [12][13][14] dance/movement therapy, [15][16][17][18] and various forms of art therapy, [19][20][21] have received less empirical attention than other CAM therapies more commonly used among adults, such as vitamin and nonvitamin supplements and mind-body therapies. 1 Although CAT research has been predominately qualitative, clinical research on CAT has expanded from purely observational science to a wider, cross-disciplinary approach that includes fields such as neuropsychiatry.…”
mentioning
confidence: 99%